Reflets de la colonialité dans la scène des musiques nouvelles - Dharmoo, Gabriel (Intersections: Canadian Journal of Music / Intersections : revue canadienne de musique, 2019)
Certains membres de la scène des musiques nouvelles souhaitent en décentrer ses racines eurocentriques et en critiquer ses tendances colonialistes. Avant même de discuter des stratégies qui pourraient constituer un cadre décolonisateur, il est utile d’identifier comment la colonialité se reflète dans cette scène. L’auteur, lui-même membre actif de celle-ci, partage des pistes de réflexion portant sur l’homogénéité culturelle du milieu, les questions d’accès, l’héritage de la musique classique, le concept de l’excellence européenne, la présomption d’universalité, la coexistence de statuts de légitimité et de marginalité, la relation ambigüe avec l’appropriation culturelle et les fondements de l’attribution du mérite.

A Rich Musical Legacy from Québec: Baroque Motets of the Ursuline and Hôtel-Dieu Monasteries of New France - MacIsaac, Elizabeth Kathleen Norah (Université de Washington, 2018)
Carefully preserved in the archives of the Ursuline and Hôtel-Dieu Monasteries of Quebec are several manuscripts containing Canada’s first sacred works for female voices. The manuscripts contain dozens of intricate motets composed in the French Baroque style, a repository of music which has not been sung for hundreds of years. These motets form a neglected part of Canada’s musical heritage which is waiting to be unearthed and explored. Ursuline and Augustinian nuns arrived to the French territories of the New World to educate and evangelize young women. Singing formed a core element of their teaching and worship. For over one hundred years (1639-1760), church music provided a backbone to Canada’s vibrant musical culture. When the French territories were lost to Britain and Spain, musical culture shifted radically and the sacred French music simply faded into obscurity. An overview of the sweeping events of the French Baroque era includes discussion of France’s social conditions, the political and religious climate, the flowering of the arts and the exploration of the New World. In France, the seventeenth and eighteenth centuries were a time of great strife which heralded the massive social changes to come in the nineteenth century. France’s struggles directly impacted the colony of New France, including that of its religious institutions and music. This study traces the musical activities in the Ursuline community of New France as the nuns lived their mission on the frontier, teaching Aboriginal and colonial girls. The evolution of female emancipation stemming from religious evangelism is considered. Examination of a trove of 160 motets located in the female monasteries of Québec City reveals the high caliber of music practiced by the nuns. No interpretive editions for performance purposes exist. Newly transcribed works have been generated from the manuscripts, with period performance guidance for appropriate ornamentation and ensemble requirements. An in-depth discussion of New France Baroque vocal and choral musical styles is provided, with reference to historical records of how it was taught, as described in contemporaneous music treatises and many original documents specific to these religious female communities.

D’exil et d’américanitude : un entretien avec Linda Bouchard - Bertrand, Simon (Circuit : musiques contemporaines, 2017)
Quebec composer Linda Bouchard (born 1957) is an extremely prolific composer, particularly active on the new music scene in the u.s. where she has lived for lengthy periods since 1989. She has composed a rich and diverse catalogue of works, ranging from orchestral music to more intimist instrumentations, and also using multimedia or improvisation. In this interview, the composer reflects on the question of exile and identity in light of her own experience, thus reliving her own artistic path while also addressing some still burning questions about the place of music creators in the global culture.
Keywords: composer; compositrice; exil; exile; identity; identité; parcours; society; société; trajectory

Björk Digital : escale à Montréal - Marcotte, Nicolas-Alexandre (Circuit : musiques contemporaines, 2017)
An article from Circuit, on Érudit.

Java to Jazz: Eva Gauthier - Spiller, Henry (Javaphilia: American Love Affairs with Javanese Music and Dance, 2015)

Providing the Taste of Learning: Nadia Boulanger’s Lasting Imprint on Canadian Music - Boivin, Jean (Intersections: Canadian Journal of Music / Intersections : revue canadienne de musique, 2013)
This article traces the rich Canadian legacy of the twentieth-century French musical legend Nadia Boulanger (1887–1979). Through teaching her more than seventy Canadian students, both French- and English-speaking, the renowned French pedagogue played a crucial role in the development of concert art music in this country from the 1920s, notably in Montreal and Toronto. Her numerous Canadian students went on to distinguish themselves as composers, teachers, performers, musicologists, theorists, administrators, and radio producers. Drawing on extensive archival and primary research, this study demonstrates the decisive impact Boulanger had on the development of musical styles and compositional practices in Canada in the last century.

« Donner le temps » : entretien avec Lorraine Vaillancourt - Goldman, Jonathan (Circuit : musiques contemporaines, 2013)
In an interview with Lorraine Vaillancourt, the founder and artistic director of the Nouvel Ensemble Moderne (nem) recounts her musical education in Quebec, Montreal and Paris, and goes on to describe the establishment and development of her ensemble, the choice of repertoire and her plans for the future.
Keywords: Lorraine Vaillancourt; Nouvel Ensemble Moderne; contemporary music ensemble; direction musicale; ensemble de musique contemporaine; musical conducting

The Vocal Music of Ana Sokolović: Love Songs for the Twenty-First Century - Bernstein, Tamara (Circuit, 2012)
Enchanted by the vocal music of Serbian-born Canadian composer Ana Sokolović, Tamara Bernstein visited the composer at her home in Montreal. Sokolović’s music draws on several sources, including the theatrical world and the culture of the Balkans. The extended vocal techniques in Sokolović’s music are rooted not in the avant-garde music of the twentieth century, but in the oral traditions and poetic voice of Serbia. It seems that the more the composer returns to her cultural roots, the more she embraces the universality of the human soul.

Violet Archer: A Canadian woman in composition - Banfield, Emma (Université Northwestern, 2010)